2021
DOI: 10.1007/s00384-021-03835-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognostic relevance of the recommended minimum number of lymph nodes in colorectal cancer—a propensity score analysis

Abstract: Purpose Nodal status in colorectal cancer (CRC) is an important prognostic factor, and adequate lymph node (LN) staging is crucial. Whether the number of resected and analysed LN has a direct impact on overall survival (OS), cancer-specific survival (CSS) and disease-free survival (DFS) is much discussed. Guidelines request a minimum number of 12 LN to be analysed. Whether that threshold marks a prognostic relevant cut-off remains unknown. Methods Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Consistent with our results, Ramser et al also found that the number of nodes examined was an independent predictor of CC prognosis. Detecting more than or equal to 12 lymph nodes could improve the prognosis of patients with CC, indicating that too few nodes examined was associated with a poor prognosis, especially in patients with grade II tumors ( 32 ). Clinically, fewer nodes examined could result in an inaccurate pathological assessment, which might influence subsequent adjuvant therapy, and further affect prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Ramser et al also found that the number of nodes examined was an independent predictor of CC prognosis. Detecting more than or equal to 12 lymph nodes could improve the prognosis of patients with CC, indicating that too few nodes examined was associated with a poor prognosis, especially in patients with grade II tumors ( 32 ). Clinically, fewer nodes examined could result in an inaccurate pathological assessment, which might influence subsequent adjuvant therapy, and further affect prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this heterogeneity, the criteria for the optimal number of lymph nodes to be dissected have not changed in less than half a century and do not consider tumor localization. Previous studies on lymph node count and survival are limited because they do not take tumor localization into account 8–12 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on lymph node count and survival are limited because they do not take tumor localization into account. [8][9][10][11][12] Moreover, the use of minimally invasive surgery for colorectal cancer has increased dramatically over the past 20 years, prompting a shift toward laparoscopic surgery from open surgery. 13 Therefore, we conducted a multicenter study to determine the prognostic impact of lymph node yield based on tumor location in patients with stage II CC who underwent laparoscopic surgery.…”
mentioning
confidence: 99%
“…been introduced to open and laparoscopic CME for colon cancer surgery in 2011 and 2013, respectively, we felt that a standardized video-based educational programme, including 3D video animations and cadaveric dissections, would help standardize the technique. A learning curve analysis was performed considering the total number of lymph nodes retrieved, which is a crucial quality marker in colon cancer surgery[13][14][15]. In a prospective study the survival rates improved as the number of the lymph nodes retrieved increased in Stage III colon cancer[14].…”
mentioning
confidence: 99%